Thermal and mechanical performance of an optimized lightweight masonry block - Luísa Costa Sousa (2014)
New building materials and modern masonry technologies are emerging in the building marketplace. Masonry, a common component with low maintenance and good durability is widely used around the world and still remains a main building material especially in developing countries. On the other hand the improvement of the thermal comfort and energy saving provides a good contribution for the development of sustainable building. The development of a new block needs to take into account the following aspects: material, overall density, thermal and mechanical requirements, geometry, topology and laying requirements, production and technological constraints. This paper describes the development a new masonry system, based on light lightweight concrete units, intended for construction of large single leaf external walls with high insulating capacity. A detailed numerical analysis and optimization has been performed from the thermal point of view. This simulation work was followed by a set of experimental tests in order to characterize the mechanical behaviour of single units and masonry specimens. The average compressive strength of the masonry obtained in compression is within the expected values required by the European Standards. (c) Civil-Comp Press, 2014.